2020
DOI: 10.1002/eat.23259
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of autism spectrum disorders are associated with longer duration of anorexia nervosa: A systematic review and meta‐analysis

Abstract: ObjectiveAnorexia nervosa (AN) is associated with neuropsychological characteristics such as impairments in central coherence, cognitive flexibility, and emotion recognition. The same features also manifest in autism spectrum disorders (ASD) and have been suggested to be associated with illness prolongation in AN. The purpose of this meta‐analysis was to examine whether pronounced neuropsychological characteristics related to ASD are associated with illness duration in AN.MethodFour databases (Medline, PsycINF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 89 publications
9
46
0
Order By: Relevance
“…Compared with other samples, however, our sample had a large proportion of individuals recently diagnosed with AN, potentially diminishing such an effect in our study. Interestingly, autistic traits were positively associated with duration of AN illness in a meta‐analysis (Saure et al, 2020). The autistic traits included in the meta‐analysis were cognitive flexibility, emotion recognition and Theory of Mind, all of which were assessed with neuropsychological testing rather than observation of social interaction such as the ADOS‐2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other samples, however, our sample had a large proportion of individuals recently diagnosed with AN, potentially diminishing such an effect in our study. Interestingly, autistic traits were positively associated with duration of AN illness in a meta‐analysis (Saure et al, 2020). The autistic traits included in the meta‐analysis were cognitive flexibility, emotion recognition and Theory of Mind, all of which were assessed with neuropsychological testing rather than observation of social interaction such as the ADOS‐2.…”
Section: Discussionmentioning
confidence: 99%
“…For example, adolescents, as well as adults, with AN display inefficiencies in nonverbal, expressive aspects of social functioning, such as facial expression (Cardi et al, 2015; Dapelo et al, 2015; Leppanen et al, 2017; Rhind, Mandy, Treasure, & Tchanturia, 2014). These inefficiencies may have important clinical implications, as they are associated with less optimal response to treatment for AN (Stewart, McEwen, Konstantellou, Eisler, & Simic, 2017; Tchanturia, Larsson, & Adamson, 2016), and a recent meta‐analysis documented a positive association between autistic traits and duration of AN (Saure et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, the AQ-10 and the original 50-item AQ may lack efficacy in distinguishing autism cases in clinical populations [38][39][40][41]. In the current study, that the AQ-10 may lack accuracy is suggested by the fact that participants in the HAT group had a lower, albeit non-significant, duration of illness compared the LAT group, whereas characteristics associated with autism assessed with experimental measures are associated with longer illness durations in AN [17]. Future research in this area should consider exploring sensory sensitivity in individuals with AN only compared to people with AN and a diagnosis of autism, or using gold-standard autism measures such as the Autism Diagnostic Observation Schedule (ADOS) known to be effective in this population [42].…”
Section: Discussionmentioning
confidence: 61%
“…Research suggests that autistic traits in AN may be associated with longer illness durations and poorer treatment outcomes, suggesting that treatment adaptations may be required. Recent qualitative research suggests that people with AN and high autistic traits may particularly benefit from adaptations addressing sensory difficulties associated with autism [16][17][18][19]. This research indicates that that sensory difficulties in autism may impact AN and its treatment in two key ways: firstly, food-related sensitivities such as an aversion to certain textures may motivate food avoidance [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have previously summarized the literature on central coherence and set‐shifting in eating disorders. However, these reviews either: (a) only looked at central coherence across eating disorder diagnoses (Lang et al, 2014a; Lopez, Tchanturia, Stahl, & Treasure, 2008a); (b) only looked at set‐shifting across eating disorder diagnoses (Roberts, Tchanturia, Stahl, Southgate, & Treasure, 2007; Wu et al, 2014); (c) only examined AN (Saure et al, 2020); (d) did not use a meta‐analysis approach (Idini, Marquez‐Medina, Pifarre, Buj‐Alvarez, & Castan‐Campanera, 2012; Kanakam & Treasure, 2013; Smith, Mason, Johnson, Lavender, & Wonderlich, 2018; van Elburg & Treasure, 2013); (e) were not in English (Solano‐Pinto, de la Pena, Solbes‐Canales, & Bernabeu‐Brotons, 2018); or (f) a combination of the above (Christensen, Bentz, Clemmensen, Strandberg‐Larsen, & Olsen, 2019; Cury et al, 2020; Fuglset, 2019; Jáuregui‐Lobera, 2014; Lang et al, 2014b; Lang et al, 2016; Miles, Gnatt, Phillipou, & Nedeljkovic, 2020; Reville, O'Connor, & Frampton, 2016; Stedal, Frampton, Landrø, & Lask, 2012; Van Autreve & Vervaet, 2015; Van den Eynde et al, 2011; Voon, 2015; Westwood, Stahl, Mandy, & Tchanturia, 2016). Thus, to date, no single paper has looked at both central coherence and set‐shifting across eating disorder diagnoses.…”
Section: Introductionmentioning
confidence: 99%